The clinicopathological and prognostic value of CD44 expression in bladder cancer: a study based on meta-analysis and TCGA data. Issue 1 (1st January 2020) - Hu, Yu; Zhang, Yongrui; Gao, Jialin; Lian, Xin; Wang, Yuantao
ABSTRACT: CD44 is reported to be involved in tumor invasion and metastasis. However, the role of cancer stem cell marker CD44 in bladder cancer still remains controversial. Hence, the correlations between CD44 expression and the clinicopathological features and the prognosis of bladder cancer were investigated. Publications using immunohistochemical methods were identified. The Cancer Genome Atlas (TCGA) data were also analyzed. The odds ratios (ORs) or hazard ratios (HRs) with their 95% confidence intervals (95% CIs) were calculated. 14 studies involving 1107 tissue samples were included. CD44 expression in bladder cancer was lower than in non-tumor tissue samples (OR = 0.14, P = 0.005), which was consistent with TCGA data. CD44 expression was correlated with advanced T stage (OR = 1.76, P = 0.029) and lymph node metastasis (OR = 4.09, P < 0.001). Multivariate survival analysis showed that CD44 expression was not linked to tumor-specific survival, overall survival, and recurrence/relapse-free survival, but was associated with disease failure (HR = 2.912, 95% CI = 1.51–5.61). No relationships of CD44 expression with the clinicopathological features and overall survival were found from TCGA data. Our finding suggested that CD44 expression may be correlated with progression, metastasis, and disease failure of bladder cancer. However, further large-scale studies are needed. Abbreviations : CD44: Cluster of Differentiation 44; CIs: Confidence Intervals; CSCs: Cancer Stem Cells; EMT: Epithelial-mesenchymal Transition; HRs: Hazard Ratios; ORs: Odds Ratios; TCGA: The Cancer Genome Atlas Graphical abstract: